Maternal use of sedative drugs and its effects on pregnancy outcomes: a Finnish birth cohort study - Satu-Maarit Björkstedt (Nature Portfolio, 2021)
Abstract Our aim was to evaluate maternal use of sedative drugs before, during, and after pregnancy and to assess the influence of use of these drugs on pregnancy outcomes. The study cohort (N = 6231) consists of all primiparous women, who lived in the city of Vantaa, Finland, and who delivered a singleton between 2009 and 2015. Data were obtained from Finnish national health registers. Of the women, 3.2% (n = 202) purchased at least once sedative drugs within 90 days before conception, during pregnancy and/or within 90 days after delivery. Sedative drug users were older, less likely to cohabitate, more often smokers, had lower educational attainment and had more mental diseases (for all p < 0.001) compared with non-users. Sedative drug users purchased more often antidepressants and drugs for the alimentary tract, musculoskeletal and nervous system than non-users (for all p < 0.001). No adverse birth or pregnancy outcomes were found in the group using sedative drugs compared with the non-users. Studies in larger cohorts are needed to confirm our study findings.